A new beginning - Eswaran, Vijay, Dato'; Balagtas,Chandravali Dasi; Munian, Maralikrishnan; VStudios ([S.l.] : VStudios, 2008)
A talk by Dato' Vijay Eswaran on 6th anniversary convention 2004 in Dubai. Talk on a new beginning of V
Title from title screen
V-Dubai
Executive producer, Pathman Senathirajah
DVD format
Keywords: Multilevel marketing; Direct marketing